Study of PLTMH development planning in sasnek village sawiat district, South Sorong Regency West Papua Province - Markus Dwiyanto Tobi; Vina N Van Harling (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Electricity is needed by the whole society. Sasnek village is one of the villages located in Sawiat District, South Sorong Regency, West Papua Province. Sasnek village is very clear and inhabited around 100KK. This village has not been served by electricity until now.  Micro-hydro power plants are small-scale power plants whose capacity presents between 100 W to 100 kW. This study will be used for loading stages with a 12 Volt DC power capacity, because it is one of the most efficient, young and safe ways. Measurement of air discharge, discharged by 2 liters / second from a measurement area of 5 m2 and an average air speed of 00.65 m / d.  However, due to the condition of the river water flowing throughout the year in the sense of never dried, then used a correction factor of 0.75. Thus the flow that can be used is equal to 0.65 m3 / d. Based on the analysis of the potential contained in Sasnek PLTMH, it can be calculated Distribution Grid sourced from Sasnek PLTMH is 10 KW.With the careful planning so that the results of its implementation will give a positive impact to be meeting the needs of electricity in the village and surrounding villages sasnek.